Hydrologic and hydraulic simulations for use in macrodrainage designs for gully management and recovery (2017)
Runoff on susceptible terrains that is not associated with adequate drainage causes soil erosion, as gullies. Gullies and drainage continue to be major issues in reclamation projects since soil erosion can be reactivated after the application of recovery measures. This paper describes a low-cost project framework for macrodrainage for a gully in Nazareno (MG, Brazil) to provide support to gully management and recovery. We used a simple methodology with the application of Geographic Information Systems (GIS) and concentrated hydrologic and hydraulic models (freely available softwares). The basin has steep slopes (8 to 20%) and the water flows mainly to the northwest, which contribute to exacerbate erosion problems. We studied the effect of environmental conditions on different simulations to elaborate a drainage system project using the free software tools. Therefore, the findings of this paper can aid gully management and recovery for this and other areas with similar issues.